2005
DOI: 10.1194/jlr.m500131-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Mannose 6-phosphate receptors, Niemann-Pick C2 protein, and lysosomal cholesterol accumulation

Abstract: Niemann-Pick disease type C (NPC), caused by mutations in the NPC1 gene or the NPC2 gene, is characterized by the accumulation of unesterified cholesterol and other lipids in endo/lysosomal compartments. NPC2 is a small, soluble, lysosomal protein that is targeted to this compartment via a mannose 6-phosphate-inhibitable pathway. To obtain insight into the roles of mannose 6-phosphate receptors (MPRs) in NPC2 targeting, we here examine the trafficking and function of NPC2 in fibroblast lines deficient in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 32 publications
(51 reference statements)
5
51
0
Order By: Relevance
“…These results support the hypothesis that, in addition to the AP-1/GGA sorting machinery (see Fig. 2) (Willenborg et al, 2005), the subcellular fate of mammalian NPC2 is also regulated by the AP-3 complex, probably by an indirect mechanism.…”
Section: Ap-3 Deficiency Leads To Decreased Detection Of Unesterifiedsupporting
confidence: 79%
See 3 more Smart Citations
“…These results support the hypothesis that, in addition to the AP-1/GGA sorting machinery (see Fig. 2) (Willenborg et al, 2005), the subcellular fate of mammalian NPC2 is also regulated by the AP-3 complex, probably by an indirect mechanism.…”
Section: Ap-3 Deficiency Leads To Decreased Detection Of Unesterifiedsupporting
confidence: 79%
“…mentioned above, hNPC2 is modified by the addition of a mannose-6-phosphate group (Naureckiene et al, 2000), which is a signal for targeting soluble molecules to the lysosome when recognized by the mannose-6-phosphate receptor (Kornfeld and Mellman, 1989;Pohlmann et al, 1995). Consistent with this modification, the targeting of NPC2 is regulated by mannose-6-phosphate receptors (Willenborg et al, 2005).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…We also found that Asn-39 is always linked to an Endo H-sensitive oligosaccharide, whereas Asn-116 is variably glycosylated both in terms of the presence and processing of the oligosaccharide. Given that NPC2 is targeted via the mannose 6-phosphate lysosomal targeting pathway (8,26,27), Endo H sensitivity of the NPC2 oligosaccharides is likely to reflect the presence of mannose 6-phosphate (23); this modification occurs temporally prior to and blocks the actions of Golgi ␣-mannosidase, which is required for conversion of N-linked glycans to Endo H-resistant forms. Thus, Asn-39 represents the primary substrate of lysosomal protein UDP-N-acetyglucosamine phosphotransferase.…”
Section: Discussionmentioning
confidence: 99%